The Effect of Halal Traceability System on Halal Supply Chain Performance - Nizamuddin Zainuddin; Adam Mohd Saifuddin; Norita Deraman; Aziam Azuan Osman (International Journal of Supply Chain Management, 2020)
Supply chain management represents a set of interdependent organisations that work closely together to manage the flow of goods or services and information along the value-added chain of products, in order to realise end customer value at the lowest possible costs. Halal Supply Chain performance measures can be developed based on existing measures of the conventional supply chain as long as the primary objective is preserving halal integrity rather than minimising cost or maximising profit. The objective of this paper is to see the effect of halal traceability system towards halal supply chain performance using SEM techniques. Halal Traceability system is a system that enables the identification of products’ and product ingredients’ halal status backward and forward, along the production chain. This article focus will be on the survey method only. The instrument development was based on a literature survey. This study focuses on the population of halal certified food and beverages (FB) manufacturers as disclose in JAKIM Halal Portal. About 254 questionnaire sets answered by the intended respondents out of 500 being distributed and no data are detected as missing. All questions are completely answered by the respondents. This study has confirmed the effect of Halal Traceability system on Halal Supply Chain performance. Having demonstrated the significance of the hypothesised effect with a substantial total variance explained (i.e. above 75 percent) and sufficient predictive relevance, this study provides strong empirical evidence that a high level of Halal Supply Chain performance can be achieved through the effective implementation of Halal Traceability system.